The Study of Platelet Indices in Acute Respiratory Tract Infections in Children Aged Between 2 Months -5 Years Visiting a Tertiary Care Hospital- A Cross-Sectional Study - Teja, Manne Sai; Karthik.S, Karthik.S; Prasad, K.N.V (Journal of Neonatal Surgery, 2025)
Background: Pneumonia is an inflammation of the lung tissue in the alveoli, caused by both infectious and non-infectious factors. Although platelets’ primary function is haemostasis, recent studies have also explored their involvement in inflammation and immune response.Objectives:This study was conducted with the objectives to determine the changes in platelet indices during an acute respiratory tract infection in children aged between 2 months to 5 years and to study the association of severity of acute respiratory tract infections with changes in platelet indices in children aged between 2 months to 5 years at the time of admission. Methodology: This was a correctional study conducted among children with respiratory tract infections aged between 2 months to 5 years at a tertiary level hospital in South India. A total of 80 children were included in the study. A sample of 1 ml of venous blood was drawn from patients visiting the hospital and sent for Complete Blood Count analysis, from which platelet indices were obtained and recorded.Results:The median age of the study participants in this study was 12 months (inter quartile range 6 – 25 months). Majority of the subjects were males (60, 75.0%) in this study. Considering the association between various platelet indices and the severity of respiratory illnesses it was found that, the platelet count increased with increase in severity of illness (p <0.001). Similarly, platelet distribution width (p = 0.002) and plateletcrit (<0.001) increased with increased severity of the illness. Meanwhile mean platelet volume decreased with increased severity of the illness. Conclusion: Platelet parameters show variation in the lower respiratory tract infections. As they can be determined as a part of routine complete blood picture analysis, they may be considered as markers of inflammation in the diagnosis of lower respiratory tract infections.